Impact of the 2015 Stock Market Crash on China’s Stock Market: Evidence from Moutai and China Construction - Luo, Hao (SHS web of conferences, 2024)
The stock market crash in 2015 had a significant impact on China’s finances, some researchers focus on the causes of the stock market crash, however, its impact on stocks does not seem to have a uniformity of trend, perhaps there are different inspirations for investors. Therefore, this paper achieves the goal of exploring the impact of the 2015 stock market crash on Chinese stocks by collecting a total of four sets of stock data on daily and weekly closing prices of Moutai and China Construction and performing ARIMA model analysis on the data to predict the logarithmic returns of the four sets of data. It was found that Moutai seemed to be less affected by the crash than China Construction. Meanwhile, after an in-depth analysis of the coping strategies and business environments of these two stocks, the study highlights that in addition to the financial position and risk management capabilities, a company’s brand and product quality, as well as market resilience, are key factors in coping with market risk. This provides investors with a more comprehensive perspective when making investment decisions.